Buzzletag / Muhammad Nor Aswad Husin ... [et al.] - Husin, Muhammad Nor Aswad; A. Radzak, Muhammad Afiffuddin; Mohd Rozi, Muhammad Alif; Che Mohd Zaki, Che Mohammad Shahid; Shiful Annuar, Asyrof Hadi; Nor Hisham, Muhammad Azim; Hashim, Siti Munirah Hariani (2022)
TIQ TAQ technology Company was established in 2021 and is based in Seremban, Negeri Sembilan. Our company produces technology products such as tracking devices. The company is wholly owned by Bumiputra, led by Muhammad Nor Aswad and assisted by board members and employees. Our company sells products online as well as orders can be made daily and deliveries will be processed within 2 working days. The target market targeted by our company is women, riders, drivers, kids and spies. The purpose of this group being targeted as our customers is because to save their time while doing their daily work by not wasting time looking for goods. In this sophisticated era, there are some tracking devices have been released at a relatively high price because the quality provided is high. Our purpose in producing our product, the Buzzletag, is to provide a high-quality tacking device at a much lower price. The production of our product is expected to make it easier for people now to buy tracking devices for the convenience of their day. The advantage of Buzzletag in addition to the low price is that this tracking device is waterproof and uses GPS. Although there are low-priced tracking devices in the market, our tracking devices are different because at low prices, users will get high quality products, waterproof and have their own applications that can be downloaded on mobile phones or laptops. We hope that with the production of Buzzletags at a much lower price compared to high-quality tracking devices, it will help users' daily affairs more smoothly.